Spatial Trend Analysis of Temperature and Rainfall and Their Perceived Impacts on Ecosystem Services in Mau Forest, Kenya (2021)
The Mau Forest Complex is an important ecosystem in Kenya providing many ecosystem services to the local communities. However, its degradation has rendered its ability to deliver its ecosystem services such as climate regulation ineffective. This study's objective was to assess the local climate trend in terms of rainfall and temperature and their perceived impacts on ecosystem services in Mau Forest, from 1984 to 2020. We obtained gridded meteorological data for the study area from the Kenya Meteorological Department and analyzed it using Mann Kendell’s test to identify significant trends in temperature and rainfall. Focus Group Discussions were also carried out to establish the people's perceptions of local climate change and its impacts on ecosystem services. The results of the study indicate no significant trend, p>0.05, in annual rainfall over time. On the other hand, the results show a significant trend, p=3.696e-06, in average annual temperature with approximately 2℃ increase. from 1984 to2020. The local climate change has seen a decline in ecosystem services, mainly water levels and agricultural produce. To cope with and mitigate the effects of climate change, there is need to emphasize establishment of agroforestry woodlots and practice of climate-smart agriculture among the forest adjacent communities